Study of green and sustainable heterogeneous catalyst produced from Javanese Moringa oleifera leaf ash for the transesterification of Calophyllum inophyllum seed oil - Ramdhani, Destania Ayu; Wega Trisunaryanti; Triyono (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
The transesterification of Calophyllum inophyllum seed oil into biodiesel using Javanese Moringa oleifera leaf ash catalyst with various reaction conditions has been completed. MA-500 (Moringa ash at 500°C for 3 h) and MA-900 (Moringa ash at 900°C for 3 h) catalysts were obtained by grinding Javanese old Moringa oleifera leaf (MP) and then calcined for 3 h at 500 and 900°C. The crude Calophyllum inophyllum seed oil was degummed (OD) prior to continue the esterification process (ODE). The MA-500 and MA-900 catalysts were tested for their activity and selectivity through the ODE transesterification with various catalyst weights (3, 6, and 9% (w/w)), reaction temperature (55, 60, and 65°C), oil: methanol mole ratio (1:3, 1:6, and 1:9), and reaction time (60, 90, 120, and 150 minutes). The results showed that the MA-500 and MA-900 catalysts contained 18.17% and 52.91% Ca respectively. The esterification reaction could reduce FFA levels to 89.82%, from 19.46% to 1.98%. ODE transesterification with MA-900 catalyst optimum reaction conditions with a catalyst weight of 3%, reaction temperature of 60°C, oil: methanol mole ratio of 1:9, and reaction time of 120 min, 76.17% FAME yield was observed. The MA-900 catalyst has the potential to be an effective green catalyst.